Analytical research of the relation between hydraulic mechanism of the axial pressure of the drilling rig and technological parameters of the drilling regimes of the geological exploration boreholes - V. V. Kulikov; S. . Zavacky (Известия высших учебных заведений: Геология и разведка, 2015)
The existing relations for definition of the axial load on the rock cutting tool by the parallel or serial mounted throttling valves, do not take into account many different flows of the hydraulic fluid through the valve, and it results in different character of the pressure losses levels related to the power. Because of this, we can not exactly evaluate variations of the axial load on the cutting tools when changing hydraulic parameters of the thrust mechanism. The flow pattern of the hydraulic fluid through the throttling valve and through the pressure shift is defined by the mechanical speed rate of the bore drilling. Flow pattern (laminar or turbulent) is necessary for the definition of the axial pressure on the cutting tool. The power index of the fluid flow through the valve or through the pressure shift is variable value, depending on the flow pattern and mechanical speed of the drilling.